Antioxidant Supplementation Does Not Affect Bone Turnover Markers During 60 Days of 6° Head-Down Tilt Bed Rest: Results from an Exploratory Randomized Controlled Trial. Issue 6 (8th April 2021) - Austermann, Katharina; Baecker, Natalie; Zwart, Sara R; Fimmers, Rolf; Frippiat, Jean-Pol; Stehle, Peter; Smith, Scott M; Heer, Martina
ABSTRACT: Background: Immobilization and related oxidative stress are associated with bone loss. Antioxidants like polyphenols, omega-3 fatty acids, vitamins, and micronutrients may mitigate these negative effects on bone metabolism through scavenging of free radicals. Objectives: We hypothesized that antioxidant supplementation during 60 days of 6° head-down tilt bed rest (HDBR) would reduce bone resorption and increase bone formation compared to nonsupplemented controls. Methods: This exploratory randomized, controlled, single-blind intervention study conducted in a parallel design included 20 healthy male volunteers (age, 34 ± 8 years; weight, 74 ± 6 kg). The study consisted of a 14-day adaptation phase [baseline data collection (BDC)], followed by 60 days of HDBR and a 14-day recovery period (R). In the antioxidant group, volunteers received an antioxidant cocktail (741 mg/d polyphenols, 2.1 g/d omega-3 fatty acids, 168 mg/d vitamin E, and 80 μg/d selenium) with their daily meals. In the control group, volunteers received no supplement. Based on their body weight, all volunteers received an individually tailored and strictly controlled diet, consistent with DRIs. We analyzed biomarkers of calcium homeostasis, bone formation, and bone resorption during BDC, HDBR, and R, as well as for 30 days after the end of HDBR. Data were analyzed by linear mixed models. Results: The antioxidant supplement did not affect serum calcium, parathyroid hormone, urinary C-telopeptide of type I collagen (CTX), urinary N-telopeptide of type I collagen, serum β–C-telopeptide of type I collagen (β-CTX), bone alkaline phosphatase, aminoterminal propeptide of type I collagen, osteocalcin, or urinary calcium excretion. In both groups, typical bed rest–related changes were observed. Conclusions: Supplementation of an antioxidant cocktail to a diet matching the DRIs did not affect bone resorption or formation during 60 days of HDBR in healthy young men. This trial was registered at clinicaltrials.gov as NCT03594799.